The Effect of Mocaf Substitution on Crispness and Organoleptic Quality of Milk Sticks - Dyah Nurul Afiyah; Riska Nurtyanto Sarbini (UNIVERSITAS ISLAM LAMONGAN, 2021)
Milk sticks are one of the dairy products that are served in the form of snacks. One of the ingredients added in making milk sticks is wheat flour which has a high amylose content. It causes the resulting milk sticks to be less crunchy. It is necessary to substitute flour with low amylose content, namely mocaf (Modified Cassava Flour). This research objective was to determine the effect of mocaf on the level of crispness and organoleptic quality of milk sticks. Milk sticks was made in animal science laboratory UNISKA Kediri by adding different percentage of flour: P0 (100% wheat flour), P1 (90% wheat flour and 10% mocaf), P2 (80% wheat flour and 20% mocaf), P3 (70% wheat flour and 30% mocaf), and P4 (60% wheat flour and 40% mocaf) in six replications. This research using completely randomized design (CRD). These results indicated that the substitution of mocaf in the manufacture of milk sticks could reduce the moisture content of the milk sticks so that the substitution of mocaf could increase the crispness. The organoleptic assessment was carried out on the parameters of color, taste, and crispness. There were no significant differences between the color and taste parameters, while the crispness showed that P0 was not significantly different from P1, but it was significantly different from P2, P3, and P4.